Effect Of Coconut Husk On Phoshate Solubilizing Bacteria And Its Carrier Based Inoculants For Growth Of Legumes - S.ANBUSELVI; GUDDU KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Bio fertilizers are also known as microbial inoculants or bio inoculants. It is a product of selected, beneficial and live microorganism which help to improve plant growth and productivity or, mainly through supply of plant nutrients. Phosphate solubilizing organisms play an important role in growth of the plants. The bio inoculants improve the shelf live and survivability of microbes in soil and stimulate the growth of the plants. The present study was to extract the phosphate solubilizing bacteria from coconut husk and its formulation in growth of pulses.